Construction of the Ideal Spouse Meaning in Surah Al-Nur [24]: 26: Critique and Solution for Choosing a Life Partner - Lestari, Aida Ayu; Lestari, Fuji; Rofi’i, Muhammad Arwani (Proceedings of International Conference on Muslim Society and Thought, 2024)
This research aims to explain the interpretation of the Quranic verse in Surah al-Nur [24]: 26 regarding the ideal spouse as a critique of the considerations commonly ingrained in society such as socioeconomic status, education, or physical appearance, and to understand the characteristics of the ideal spouse contained in the verse. This study is a library research using the ’ulum al-Qur’an approach. The primary data used is the Quranic verse in Surah al-Nur [24]: 26 and several commentaries, while other supporting data are from books, articles, dictionaries, and encyclopedias. The method used is descriptive-analytical, presenting and explaining the findings. Based on this research, it is concluded that Allah promises that good people will be given good spouses, and vice versa. This study identifies the characteristics of the ideal spouse promised by Allah in Surah al-Nur [24]: 26, including having strong faith, avoiding bad and despicable qualities, being just, preserving each other, loving each other, and having similar behavior and outlook on life. The implication of this research is to provide a deeper understanding of the ideal spouse according to the teachings of the Qur’an, the importance of loyalty and quality relationships, the need for shared values and beliefs in marriage, and criticism of worldly considerations in choosing a life partner. Thus, this research provides a more comprehensive view of how the Qur’an teaches about the ideal spouse and its implications in daily life.